DIFFERENTIATED INSTRUCTION IN ISLAMIC RELIGIOUS EDUCATION TO FOSTER STUDENT CREATIVITY WITHIN THE MERDEKA CURRICULUM - Nasrodin Nasrodin; Riza Faishol; Ainur Rofiq (International Conference on Humanity Education and Society (ICHES), 2025)
Students come to class with diverse backgrounds, readiness levels, interests, and learning styles. This diversity has the potential to foster creativity if managed properly. Unfortunately, learning in schools still tends to be uniform, so the unique potential of students is often overlooked. The Merdeka Curriculum introduces differentiated instruction that adapts content, process, and product to student characteristics based on diagnostic assessments. This study aims to describe the implementation of differentiated learning in the subject of Islamic Religious Education and Character Education within the Merdeka Curriculum to foster student creativity. The research design uses a qualitative approach with a case study at SMPN 1 Cluring. Data were collected through interviews, observations, and documentation, then analyzed using Miles and Huberman’s interactive model. Data validity was maintained through source and method triangulation. The results show that the implementation of the Merdeka Curriculum at SMP Negeri 1 Cluring is carried out through three main stages: planning, implementation, and evaluation. Overall, the application of differentiated learning has been proven to enhance student creativity, as evidenced by increased willingness to ask questions, active participation in discussions, the ability to produce creative works, and improved collaboration.